Residual OXPHOS is required to drive primary and metastatic lung tumours in an orthotopic breast cancer model - Herst, Patries; Carson, Georgia; Lewthwaite, Danielle; Eccles, David; Schmidt, Alfonso; Wilson, Andrew; Grasso, Carole; O’Sullivan, David; Neuzil, Jiri; McConnell, Melanie; Berridge, Michael (Frontiers in Oncology, 2024)
Background. Fast adaptation of glycolytic and mitochondrial energy pathways to changes in the tumor microenvironment is a hallmark of cancer. Purely glycolytic ρ 0 tumor cells do not form primary tumors unless they acquire healthy mitochondria from their micro-environment.Here we explored the effects of severely compromised respiration on the metastatic capability of 4T1 mouse breast cancer cells. Methods. 4T1 cell lines with different levels of respiratory capacity were generated; the Seahorse extracellular flux analyser was used to evaluate oxygen consumption rates, fluorescent confocal microscopy to assess the number of SYBR gold-stained mitochondrial DNA nucleoids, and the presence of the ATP5B protein in the cytoplasm and fluorescent in situ nuclear hybridization was used to establish ploidy. MinION nanopore RNA sequence analysis was used to compare mitochondrial DNA transcription between cell lines. Orthotopic injection was used to determine the ability of cells to metastasize to the lungs of female Balb/c mice. Results. OXPHOS-deficient ATP5B-KO3.1 cells did not generate primary tumors. Severely OXPHOS compromised ρ 0 D5 cells generated both primary tumors and lung metastases. Cells generated from lung metastasis of both OXPHOS-competent and OXPHOS-compromised cells formed primary tumors but no metastases when re-injected into mice. OXPHOS-compromised cells significantly increased their mtDNA content, but this did not result in increased OXPHOS capacity, which was not due to decreased mtDNA transcription. Gene set enrichment analysis suggests that cells derived from lung metastases downregulate their epithelial-to-mesenchymal related pathways. Conclusion. In summary, OXPHOS is required for tumorigenesis in this orthotopic mouse breast cancer model but even very low levels of OXPHOS are sufficient to generate both primary tumors and lung metastases.